2022
DOI: 10.1101/2022.11.19.517186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urine proteomic analysis of the rat e-cigarette model

Abstract: Urinary proteomics was used to investigate the potential effects of e-cigarettes on the human body. In this study, a rat e-cigarette model was constructed by smoking for two weeks and urine samples before, during, and after e-cigarette smoking were collected. Urine proteomes before-after smoking of each rat were compared individually, while the control group was set up to rule out differences caused by rat growth and development. After smoking, the differential proteins produced by rats shows strong individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…OBP2A was identified in a total of 3 rats in the Day10 and Day14 groups, and 2 of them showed a down-regulation trend. This protein was also identified in the rat e-cigarette model, and the changes in the expression of this protein showed strong consistency among the six rats [13] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OBP2A was identified in a total of 3 rats in the Day10 and Day14 groups, and 2 of them showed a down-regulation trend. This protein was also identified in the rat e-cigarette model, and the changes in the expression of this protein showed strong consistency among the six rats [13] .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are few studies on the effects of different odors on the rat urinary proteome. In a previous study, multiple isoforms of odor-binding proteins were identified in the urinary proteins of rats after smoking jasmine-flavored e-cigarettes, suggesting that the urinary proteome has the ability to reflect changes in the organism after smelling odors [13] . So do rats produce different changes after smelling different odors?…”
Section: Introductionmentioning
confidence: 99%
“…Portions of this text were previously published as part of a preprint ( Liu et al, 2022 ). Eleven SPF (specific pathogen free) 8-week-old healthy male Wistar rats (180–200 g) were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. (Beijing, China), with the animal licence number SYXK (Jing) 2021-0011.…”
Section: Methodsmentioning
confidence: 99%